Trans Arterial Embolization of Spontaneous Abdominal Muscle Bleeding - Biondetti, Pierpaolo; Amato, Gaetano Valerio Davide; Lanza, Carolina; Carriero, Serena; Ascenti, Velio; Grilli, Chiara; Xhepa, Edon; Angileri, Salvatore Alessio; Ierardi, Anna Maria; Carrafiello, Gianpaolo (Journal of Endovascular Resuscitation and Trauma Management, 2025)
Spontaneous abdominal muscle bleeding is an uncommon condition that usually arises in elderly and fragile patients. Commonly affected areas include body wall muscles, particularly the rectus sheath and the iliopsoas, with clinical manifestations such as abdominal pain, groin pain, anemia, and in severe cases, hemorrhagic shock. A computed tomography multiphase scan is the preferred modality of examination, as it allows the characterization of hematomas and the assessment of active bleeding. Conservative management of coagulopathy is standard care for stable patients while embolization and surgical options are reserved for those with hemodynamic instability or significant bleeding. Current literature provides incongruous results on outcomes, while some authors consider embolization only after conservative treatment failure, other authors advocate for a more aggressive approach in patients who are at high risk of developing a poor outcome. This discrepancy underlines the need for further standardized research to optimize management approaches in this fragile patient population.